The Bone Morphogenetic Protein Signaling Inhibitor LDN-193189 Enhances Metastasis Development in Mice - Vollaire, Julien; Machuca-Gayet, Irma; Lavaud, Jonathan; Bellanger, Aurélie; Bouazza, Lamia; El Moghrabi, Soumaya; Treilleux, Isabelle; Coll, Jean-Luc; Peyruchaud, Olivier; Josserand, Véronique; Cohen, Pascale A. (Frontiers in Pharmacology, 2019)
Breast cancer with bone metastasis is essentially incurable with current anticancer therapies. The bone morphogenetic protein (BMP) pathway is an attractive therapeutic candidate, as it is involved in the bone turnover and in cancer cell formation and their colonization of distant organs such as the bone. We previously reported that in breast cancer cells, the ZNF217 oncogene drives BMP pathway activation, increases the metastatic growth rate in the bone, and accelerates the development of severe osteolytic lesions in mice. In the present study, we aimed at investigating the impact of the LDN-193189 compound, a potent inhibitor of the BMP type I receptor, on metastasis development in vivo. ZNF217-revLuc cells were injected into the left ventricle of nude mice (n = 16) while control mice (n = 13) were inoculated with control pcDNA6-revLuc cells. Mice from each group were treated or not with LDN-193189 for 35 days. We found that systemic LDN-193189 treatment of mice significantly enhanced metastasis development, by increasing both the number and the size of metastases. In pcDNA6-revLuc-injected mice, LDN-193189 also affected the kinetics of metastasis emergence. Altogether, these data suggest that in vivo, LDN-193189 might affect the interaction between breast cancer cells and the bone environment, favoring the emergence and development of multiple metastases. Hence, our report highlights the importance of the choice of drugs and therapeutic strategies used in the management of bone metastases.